(untitled) (INCH : Journal of Infant and Child Healthcare, 2023)
The Indonesian maternal mortality rate in 2019 is high, namely 305/100,000 live births, even though the 2015 MMR target is 102/100,000. Morbidity can affects mortality. Complications during pregnancy can cause pain. Coronavirus disease has the potential to increase morbidity and mortality. The purpose of this study to determine the incidence of morbidity and health of pregnant women in Pekanbaru City during the Covid-19 pandemic. This research is a descriptive study with a cross-sectional design. The population of this study were pregnant women at 12 health centers in Pekanbaru City, with a total sampling of 225 samples. The results of the study found that the morbidity of pregnant women with preeclampsia/eclampsia was 14.2%, bleeding was 2.7% and hyperemesis was 17.8%, while pregnant women in the last 1 month had preeclampsia/ eclampsia was 11.6%, bleeding 2, 2% and hyperemesis 22.7%. Pregnant women with hypertension before pregnancy was 0.4% and during pregnancy was 3.1%, while pregnant women with edema was 1.3%. Pregnant women who consumed herbal medicine was 15.6%, consumed iron tablets was 59.6% and did pregnancy exercise 10.7%.